Manfaat Lidah Buaya Sebagai Anti Penuaan Melalui Aktivitas Antioksidan - Christine Yohana Sianturi (Essence of Scientific Medical Journal, 2019)
Introduction: Elderly population in Indonesia is predicted to increase every year. Aging itself is a process of decreasing physiological integrity that triggers dysfunction and increases the risk of death. One theory of aging is oxidative stress due to free radicals, which can be prevented by increasing antioxidants, including herbs such as aloe vera. Discussion: Excessive free radicals trigger oxidative stress and cause biomolecular damage to cells. Free radicals are neutralized by antioxidant system which reduces peroxide concentration, affects metabolism, and improves membrane oxidation. Aloe vera contains polysaccharides, specifically mannose-6-phosphate and flavonoids, like kaempeferol, quercertin, and merycerin, which act as antioxidants.. Conclusion: The content of polysaccharides and aloe vera flavonoids acts as an antidote to various free radicals which cause the aging process. Keywords: Aloe vera, free radical, antioxidant